2022
DOI: 10.1039/d2lc00527a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic dissection ofStentor coeruleusin a microfluidic cross junction

Abstract: Stentor coeruleus, a single-cell ciliated protozoan, is a model organism for wound healing and regeneration studies. Despite Stentor’s large size (up to 2 mm in extended state), microdissection of Stentor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The deformability is measured by imaging single-cell geometric changes under the shear stress [93][94][95] or extensional forces. [96][97][98] The accu-racy of cell classification can be improved by combining mechanical typing and deformation dynamics with cell morphology. For example, Otto et al 22 reported a real-time cell deformability cytometry platform (RT-DC) that uses highspeed imaging to measure cell deformability under shear force (Fig.…”
Section: Image-based Methodsmentioning
confidence: 99%
“…The deformability is measured by imaging single-cell geometric changes under the shear stress [93][94][95] or extensional forces. [96][97][98] The accu-racy of cell classification can be improved by combining mechanical typing and deformation dynamics with cell morphology. For example, Otto et al 22 reported a real-time cell deformability cytometry platform (RT-DC) that uses highspeed imaging to measure cell deformability under shear force (Fig.…”
Section: Image-based Methodsmentioning
confidence: 99%